Invariant Valpha14 chain NKT cells promote Plasmodium berghei circumsporozoite protein-specific gamma interferon- and tumor necrosis factor alpha-producing CD8+ T cells in the liver after poxvirus vaccination of mice. - Korten, S; Anderson, R; Hannan, C; Sheu, E; Sinden, R; Gadola, S; Taniguchi, M; Hill, A (2005)
Understanding the protective mechanism in the liver induced by recombinant vaccines against the pre-erythrocytic stages of malaria is important for vaccine development. Most studies in mice have focused on splenic and peripheral blood T cells and identified gamma interferon (IFN-gamma)-producing CD8+ T cells as correlates of protection, which can be induced by prime-boost vaccination with recombinant poxviruses. Invariant natural killer T (Valpha14iNKT) cells can also protect against liver stage malaria, when activated, and are abundant in the liver. Since poxviruses have nonspecific immunomodulating effects, which are incompletely understood, we investigated whether recombinant poxviruses affect the protective properties of hepatic Valpha14iNKT cells and thus vaccine efficacy. We show that intradermal vaccination with recombinant poxviruses activated Valpha14iNKT cells and NK cells in the livers of BALB/c mice while inducing IFN-gamma- and tumor necrosis factor alpha (TNF-alpha)-producing pre-erythrocytic stage antigen-specific CD8+ T cells. Greater numbers of hepatic Valpha14iNKT cells secreted interleukin-4 than IFN-gamma. Vaccinated Valpha14iNKT-cell-deficient mice had lower, but still protective levels of hepatic and splenic IFN-gamma+ and TNF-alpha+ CD8+ T cells and better protection rates later after challenge with Plasmodium berghei sporozoites. Therefore, vaccine-activated hepatic Valpha14iNKT cells help in generating specific T cells but are not required for protection induced by recombinant poxviruses. Furthermore, double-positive INF-gamma+/TNF-alpha+ CD8+ T cells were enriched in protected livers, suggesting that cells expressing both of these cytokines may be most relevant for protection.